The Effect of Good Corporate Governance and Sustainability Reporting on Firm Value with Profitability as a Mediating Variable in Energy Sector Companies Listed on the Indonesia Stock Exchange - Andrie Kurniawan; Devy Sofyanty; Bryan Givan (Sean Institute, 2026)
This study examines the effect of Good Corporate Governance and Sustainability Reporting on firm value with profitability as a mediating variable in energy sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. Using panel data from annual and sustainability reports, the study employs panel regression and mediation analysis to assess the direct and indirect relationships among the variables. The findings indicate that Good Corporate Governance and Sustainability Reporting are positively associated with profitability, suggesting that stronger governance mechanisms and sustainability disclosure contribute to improved financial performance. However, neither Good Corporate Governance nor Sustainability Reporting exerts a positive direct effect on firm value. Profitability also does not mediate the relationship between governance and sustainability practices and firm value, indicating that improvements in internal performance are not automatically translated into higher market valuation. These results imply that firm value in the energy sector is more strongly influenced by external market conditions and investors’ expectations regarding the sustainability of earnings than by governance quality and sustainability disclosure alone.